2019
DOI: 10.1136/bmjopen-2019-029565
|View full text |Cite
|
Sign up to set email alerts
|

German translation, cultural adaption and validation of the unidimensional self-efficacy scale for multiple sclerosis: a study protocol

Abstract: IntroductionSelf-efficacy refers to individuals’ confidence in their ability to perform relevant tasks to accomplish desired goals. This is independent of their actual abilities. In people with multiple sclerosis (MS), self-efficacy has been shown to powerfully influence motivation and health-related behaviour, such as adherence to prescribed treatment or physical activity. So far, a rigorously tested German language self-efficacy questionnaire for people with MS is missing.MethodsThe purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 75 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…A random cross-sectional cohort of patients with clinically definite MS in accordance with the McDonald’s criteria [ 9 ] version valid at the time of their diagnosis presenting any MS phenotype was recruited into this study. PwMS of any ethnicity with very good German language skills, aged ≥18 years with different levels of functioning were included (EDSS scores from 0 (no disability) to 9.0 (severe disability); the detailed study protocol can be found elsewhere [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…A random cross-sectional cohort of patients with clinically definite MS in accordance with the McDonald’s criteria [ 9 ] version valid at the time of their diagnosis presenting any MS phenotype was recruited into this study. PwMS of any ethnicity with very good German language skills, aged ≥18 years with different levels of functioning were included (EDSS scores from 0 (no disability) to 9.0 (severe disability); the detailed study protocol can be found elsewhere [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…These included the German language versions of the General Self-E cacy Scale (GSE) (13), Resilience Scale (RS-13) (14), Multiple Sclerosis International Quality of Life (MusiQoL) (15), Hospital Anxiety Depression Scale (HADS) (16,17) and Neurological Fatigue Index Multiple Sclerosis (NFI-MS) (18). Scoring and psychometric properties of these scales are described in detail in the study protocol (10).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Cross-cultural equivalence between the USE-MS and USE-MS-G was accomplished in the semantic, idiomatic, experiential and conceptual areas (21,22). Qualitative content analysis of the verbatim interview transcriptions was performed (described in detail elsewhere (10)). During all stages of the iterative adaption process of the USE-MS-G, consensus was reached with the original scale developers (5).…”
Section: Translation Face and Content Validity And Cultural Adaptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with the recognition of the importance of self-efficacy for coping with multiple sclerosis and the fact that this disease has many features that do not occur in other chronic diseases, the need for a scale measuring the level of self-efficacy specific for this group of patients was recognized (Bonino et al, 2018;Seebacher et al, 2019). One of the first questionnaires examining the level of this variable in people with MS, following the scale proposed by Schwartz and colleagues (1996), is the Liverpool Self-efficacy Scale (LSES; Airlie, Baker, Smith, & Young, 2001).…”
Section: Introductionmentioning
confidence: 99%